Enantioconvergent Cross‐Couplings of Alkyl Electrophiles: The Catalytic Asymmetric Synthesis of Organosilanes. Issue 11 (6th February 2019) - Schwarzwalder, Gregg M.; Matier, Carson D.; Fu, Gregory C.
Abstract: Metal‐catalyzed enantioconvergent cross‐coupling reactions of alkyl electrophiles are emerging as a powerful tool in asymmetric synthesis. To date, high enantioselectivity has been limited to couplings of electrophiles that bear a directing group or a proximal p/π orbital. Herein, we demonstrate for the first time that enantioconvergent cross‐couplings can be achieved with electrophiles that lack such features; specifically, we establish that a chiral nickel catalyst can accomplish Negishi reactions of racemic α‐halosilanes with alkylzinc reagents with good enantioselectivity under simple and mild conditions, thereby providing access to enantioenriched organosilanes, an important class of target molecules. Abstract : Enantioconvergent cross‐couplings with electrophiles that lack a directing group or a proximal p/π orbital were achieved for the first time. Specifically, a chiral nickel catalyst can accomplish Negishi reactions of racemic α‐halosilanes with alkylzinc reagents with good enantioselectivity under simple and mild conditions, thereby providing access to enantioenriched organosilanes, an important class of target molecules.